Analisis Pengaruh Kebijakan Deviden dan Struktur Modal terhadap Nilai Perusahaan dengan Profitabilitas sebagai Pemoderasi pada Perusahaan Perbankan yang Listing di BEI - M Rimawan; Puji Muniarty; Alwi Alwi; Hanifah Mutiah; Aliah Pratiwi (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
The purpose of this study was to determine the effect of capital structure and dividend policy on firm value with profitability as a moderating variable in banking companies listed on the Indonesia Stock Exchange. The research design used is quantitative research. The data used is secondary data in the form of time series data. Data analysis used Smart PLS software version 3.0. The research results show that: 1). Dividend policy has no significant effect on firm value; 2). Capital structure has no significant effect on profitability; 3) Capital structure has a significant effect on profitability; 4). Dividend policy has a significant effect on profitability; 5). Profitability has a significant effect on firm value; 6). Profitability does not have a significant role in mediating the effect of capital structure and dividend policy on firm value.